Seguimiento al sistema operado por el Departamento Administrativo del Medio Ambiente (DAMA) para el monitoreo de ruido del Aeropuerto Internacional El Dorado de Bogotá - Hernández, Juan Carlos Rincón; Vargas, Julio César Domínguez (Tecnogestión: Una mirada al ambiente, 2006)
In Bogota to try to make a control of noise different tools exist SystemGEMS handled by the DAMA (Global Enviroment Monitoring Sistem)is an integrated weather station that automatically gathers the weatherdatas simultaneously that every day gathers the sonorous data, these datacan be arranged hourly or at intervals shorter, according to the necessitiesof the airport, the system has a software for the registry of complaints ofcomplete form and it files, locating them the complaint automatically, the entrance of data is fast and permanent the information.